Novel and Facile Synthesis of Biodegradable Plastic Films from Cornmeal by Using the Microwave Polymerization Technique. (18th October 2022) - Imran Din, Muhammad; Ahmed, Mahmood; Ahmad, Muhammad; Ghaffar, Tayabba; Hussain, Zaib; Khalid, Rida; Samad, Abdul
Abstract : Millions of tons of plastic are produced annually, but a major portion of plastic waste remains unrecycled. The uncycled plastic ultimately becomes a major source of solid trash and releases a variety of chemicals into our environment which can adversely affect the human health and marine life. In this study, a novel approach has been opted to synthesize a biodegradable plastic by using the microwave polymerization technique. In this novel approach, raw material (cornmeal), plasticizer (glycerin), and additive (vinegar) have been combined together to fabricate biodegradable plastic films from the microwave polymerization method. A number of rheological properties such as shear stress (Pa), shear rate (1/s), strain, and viscosity (Pa.s) of newly synthesized plastic were studied. These properties confirmed the presence of a shear thinning effect in the biodegradable plastic films on the basis of flow behavior of cornmeal. In order to check the water uptake ability and biodegradability of the cornmeal-based plastic films, water uptake and biodegradation tests were carried out. The fabricated films were neat, thin, and chewable and demonstrate promising characteristics. Therefore, these synthesized films can potentially become a suitable candidate in the packaging industry.